Physical disabilities in nursing – The use of selected tools in monitor physically disabled patien´s needs - Neugebauer, Jan; Tóthová, Valérie (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2019)
IntroductionThe multidisciplinary concept of physical disability (in comparison with other disabilities, such as mental or social) is considered less problematic. In nursing, we can point out many variables (incontinence, a higher risk of decubitus ulcers, spasticity, etc.) whose combination can be called physical disability. Goal: The goal of this study is to map selected evaluation and measuring tools that can be applied in the assessment of physically disabled patients’ needs. Methods: This review study was carried out to map selected evaluating tools for the assessment of physically disabled patients’ needs. The data were gained from academic databases of Scopus, Web of Science, Wiley Online Library, Science Direct, Ebsco and Pubmed between 2015 and 2019. After the classification by the established criteria, we identified 12 relevant sources. Results: We found 5 possibly relevant tools for the assessment of physically disabled patients’ needs. The specific tools were WHODAS 2.0, MDS, MDS-BV, SDS and ICF. Conclusions: All identified tools can be used for the assessment of physically disabled patients and are suitable for implementation in clinical practice. It was necessary to carry out this study in the Czech clinical practice to learn the effectiveness, usefulness, validity, reliability, specifics and sensitivity of selected tools
Tělesné znevýhodnění v ošetřovatelství - Využití vybraných nástrojů k monitorování potřeb pacientů s tělesným znevýhodněním
Keywords: Model Disability Sheehan Disability Scale; Model Disability Survey – Brief version; Nursing; Survey; The International Classification of Functioning, Disability and Health; Physical disability; WHODAS 2.0; Model Disability Sheehan Disability Scale; Model Disability Survey – Brief version; Nursing; Survey; The International Classification of Functioning, Disability and Health; WHODAS 2.0